Coupling Sensitive Nucleic Acid Amplification with Commercial Pregnancy Test Strips. Issue 4 (19th December 2016) - Du, Yan; Pothukuchy, Arti; Gollihar, Jimmy D.; Nourani, Armin; Li, Bingling; Ellington, Andrew D.
Abstract: The detection of nucleic acid biomarkers for point‐of‐care (POC) diagnostics is currently limited by technical complexity, cost, and time constraints. To overcome these shortcomings, we have combined loop‐mediated isothermal amplification (LAMP), programmable toehold‐mediated strand‐exchange signal transduction, and standard pregnancy test strips. The incorporation of an engineered hCG–SNAP fusion reporter protein (human chorionic gonadotropin‐O 6 ‐alkylguanine‐DNA alkyltransferase) led to LAMP‐to‐hCG signal transduction on low‐cost, commercially available pregnancy test strips. Our assay reliably detected as few as 20 copies of Ebola virus templates in both human serum and saliva and could be adapted to distinguish a common melanoma‐associated SNP allele (BRAF V600E) from the wild‐type sequence. The methods described are completely generalizable to many nucleic acid biomarkers, and could be adapted to provide POC diagnostics for a range of pathogens. Abstract : Alternative use for pregnancy test strips: By engineering a fusion reporter protein of human chorionic gonadotropin (hCG) and the SNAP protein, a hCG–DNA conjugate was synthesized. In addition, isothermal amplification assays were coupled to strand‐exchange nucleic acid transducers and thereby hCG signals were generated that can be directly read by off‐the‐shelf pregnancy test strips.